New philosophy for new media - Hansen, Mark B. N. (EBSCOhost eBook Collection, 2004)
From image to body. Between body and image : on the "newness" of new media art -- Framing the digital image : Jeffrey Shaw and the embodied aesthetics of new media -- The automation of sight and the bodily basis of vision. The affect-body. Affect as interface : confronting the "digital facial image" -- What's virtual about VR? "reality" as body-brain achievement -- The affective topology of new media art. Time, space, and body. Body times